GLOBAL TRENDS IN EDUCATIONAL POLICY IMPLEMENTATION AND THE COMPLEXITY OF QUALITY IN EDUCATION: A CAMEROONIAN PERSPECTIVE - Primus Demboh; Diah Susanti (Science Education, Institut Agama Islam Negeri Ponorogo, 2021)
This article argues that effective policy implementation strategies based on the concepts of equity, flexibility, accountability, creativity and innovation can raise students’ learning and bring about a significant economic and social development. Cameroon is an example of an education system that has over the years developed very important policies in the hope of raising the quality of knowledge that students learn in schools. The country’s education sector strategy for 2020/2030 has a good number of policies which are aimed at developing skills and promoting the spirit of entrepreneurship in the learners from the primary through the secondary to higher levels. However, most of these policies have either failed or have taken a far longer time to attain their set objectives. Cameroon like many other countries in Africa, Asia, and the rest of the world seem to present a mismatch between their educational policy objectives and what is implemented in the field. This situation is very much unlike the case in many other countries where effective educational reforms have brought about measurable growth in their economies. As a result of the numerous and diverse challenges involved in this process, very few systems attain a significant level of success in these policies. Thus, they fail because of their inability to handle the various challenges that come with the struggle for quality in education reform. This study focuses on some of those challenges that are likely to be faced by any educational system, in their struggle to achieve quality in their education; why these challenges arise and how some systems have overcome them to attain their objectives. Based on the case study of Cameroon, the study comes up with a number of factors of failures in most systems. It is built on the idea that challenges are always part of the process of education, and success can only be achieved by braving them